2014
DOI: 10.1002/ejhf.105
|View full text |Cite
|
Sign up to set email alerts
|

Burden of new hospitalization for heart failure: a population‐based investigation from Italy

Abstract: Aims Heart failure has been described as one of the emerging pandemics of the 21st century. This report aims to measure the burden of new hospitalization for heart failure in the population of an Italian region of nearly 10 million inhabitants. Methods and results Data were retrieved from healthcare utilization databases covering the population of the Italian region of Lombardy. We identified patients who were hospitalized for the first time with a primary diagnosis of heart failure (hospitalized heart failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
43
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 39 publications
(73 reference statements)
9
43
2
3
Order By: Relevance
“…Per‐patient per‐year (PPPY) inpatient, outpatient and pharmacy resource utilization and costs to treat EHMs in each of the EU5 were obtained from the literature, national databases and fee schedules, or expert opinion if otherwise unavailable (Table ). All costs were adjusted to 2016 euros (€), using a pound sterling to euro exchange rate of 1.15.…”
Section: Methodsmentioning
confidence: 99%
“…Per‐patient per‐year (PPPY) inpatient, outpatient and pharmacy resource utilization and costs to treat EHMs in each of the EU5 were obtained from the literature, national databases and fee schedules, or expert opinion if otherwise unavailable (Table ). All costs were adjusted to 2016 euros (€), using a pound sterling to euro exchange rate of 1.15.…”
Section: Methodsmentioning
confidence: 99%
“…40 In fact, the incidence of almost 37.5 heart failure cases every 10 000 person years observed in our study does not substantially differ from rates reported by available population based studies. 41 Still, even with some outcome misclassification, 42 this is expected to be non-differential-that is, independent of current use of NSAIDs-leading to a bias moving estimated associations towards the null. 43 However, non-differential misclassification (of outcome or exposure) might lead to inflated observed associations due to chance alone.…”
Section: Dose Class Celecoxibmentioning
confidence: 99%
“…Details of healthcare utilization databases of the Lombardy Region and of their use in the field of cardiovascular diseases have been reported elsewhere. 4,7,10,11 these, those who received at least 1 antihypertensive drug prescription during 2005 were identified, and the first dispensation was defined as the index prescription. Antihypertensive drugs included diuretics, angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, β-blockers, and calcium-channel blockers (CCBs) initially dispensed as monotherapy.…”
Section: Settingmentioning
confidence: 99%
“…7 However, few investigations have so far assessed the effect of adherence with antihypertensive treatment on the risk of HF in the setting of clinical practice 8 making the real-world evidence on this issue still incompletely known. This is an important gap of knowledge because HF is (1) the most common cause of hospitalization in the elderly, 9 with a high hospital readmission, mortality rate, 10,11 and cost 12 and (2) more and more frequently diagnosed 13 because of ageing of the population and better survival of patients from an acute coronary event.…”
mentioning
confidence: 99%